Secure e-transactions protocol preserving privacy for customers and bidders - Han, Song; Chang, Elizabeth; Dillon, Tharam S. (Springer, 2005)
Online transactions using mobile agents need secure protocols to help these mobile agents to accomplish the transactions initiated by a client in electronic commerce. However, the mobile agent could encounter a hostile environment. For example, a server may compromise the mobile agent and try to obtain private information from the client. A solution to tackle this issue has been proposed. The existing solution is implemented using RSA signatures that result in long signatures and heavy workloads for the mobile agent. Mobile agents will migrate from the client to a server and from one server to another in order to accomplish the client's transaction plan. Therefore, it will be interesting to re-approach this issue. We present a new scheme for secure transactions using mobile agents in potentially hostile environments. This transaction scheme is implemented by using a new undetachable signature scheme. The new undetachable signature protocol utilizes short signatures, which is desirable for low-bandwidth and efficient mobile communications.